Peran dan Fungsi Manajer Keperawatan di Puskesmas - Ricky Riyanto Iksan; Roza Indra Yeni; Rima Berlian Putri; Wiwie Herdalisa; Salamah Thomasita Batubara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the role and function of the nursing manager at the puskesmas. The method used is a case study with a situational analysis of data obtained through interviews and document studies. The stages start from assessment, problem identification, problem analysis, problem priority setting and making a plan of action. The intervention starts with drafting guidelines and self-assessment, hiring experts, outreach and evaluation. The study results indicate that the nursing manager's role and function can be improved by developing guidelines and self-assessment referring to the literature, which includes three main managerial roles and five management functions with an average self-assessment value of 95%, which can be implemented. In conclusion, the role and function of the head of nursing are vital in supporting nursing governance and improving nurse performance. Keywords: Management Function, Nursing, Manager, Role